Synthesis of magnetic nanocomposite adsorbent for removal of Pb(II) ion from wastewater: absorption modeling and optimizing - Fateme Jiryaei Sharahi; Afsaneh Shahbazi; Zohreh Bahrami (شیمی کاربردی روز, 2016)
In this study, a magnetic nanocomposite based on amino-functionalized magnetic nanoparticles (Fe3O4-NH2) is synthesized by Grafting and Solvothermal methods.  This nanocomposite is used as an adsorbent for the removal of Pb(II) ion from wastewater. Then, X-ray powder diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) techniques are implemented for investigations of structural changes of synthesized magnetic nanocomposite. Moreover, response surface methodology (RSM) is applied to obtain an optimal response of the interactions between the most important parameters in removal of Pb(II) by using Fe3O4-NH2. Experimental results demonstrated that the maximum adsorption capacity and removal efficiency in optimal conditions, such as the (initial concentration Pb(II) (187 mg/g), temperature (40 °C), adsorbent dosage (1.5 g‌/l) and pH=4.9) obtained (133.43 mg/g) and (96%) respectively. According to the thermodynamic parameters ΔH and ΔG, adsorption process was spontaneous and endothermic. In addition, the experimental data are analyzed by using the Langmuir and Freundlich isotherm models and the maximal equilibrium uptake capacity is obtained 169.5 mg/g. Finally, kinetic studies showed that the equilibrium time occurred at 90 minutes and the adsorption process by a good agreement with the second-order kinetic model with the highest values of R2 and K2=4.9 (g/mg min). This study showed that a magnetic nanocomposite based on Fe3O4-NH2 can be employed as an efficient adsorbent for the removal of Pb(II) from contaminated water sources.